Aqua-{2-morpholino-N-[1-(2-pyrid-yl)ethyl-idene]ethanamine-κN,N',N''}bis-(thio-cyanato-κN)nickel(II). - Suleiman G, N.; Ikmal H, N.A.; Khaledi, H.; Mohd A, H. (International Union of Crystallography, 2010)
In the title compound, [Ni(NCS)(2)(C(13)H(19)N(3)O)(H(2)O)], the Ni(II) ion is six-coordinated by the N,N',N''-tridentate Schiff base, the N atoms of two thio-cyanate ligands and one water O atom in a distorted octa-hedral geometry. Intra-molecular C-H⋯N and C-H⋯O hydrogen bonds occur. In the crystal, O-H⋯S, O-H⋯O and C-H⋯S hydrogen bonds link adjacent mol-ecules into layers parallel to the ac plane.